Penetrating sacral injury with a metallic pipe: a case report and literature review - Mahnjeong Ha; Kyoung Hyup Nam; Jae Hun Kim; In Ho Han (Journal of Trauma and Injury)
Other than gunshot injuries, sacral penetrating injuries with a foreign body exiting to the other side are extremely rare. We encountered a case of sacral injury in which a long metallic pipe penetrated from the anus into the lower back of a patient. Since the pelvis contains various organs, management of a penetrating injury requires multidisciplinary treatment involving several medical specialties. Due to the infrequency of this type of injury, there are no definitive guidelines for effective management. We described our experience surgically treating a sacral penetrating injury and conducted a literature review. On this basis, we suggest a surgical strategy for treating this type of injury.